The Tree Cricket Neoxabea brevipes Rehn, 1913 (Orthoptera: Gryllidae: Oecanthinae) from the Brazilian southern Atlantic Forest: morphology, bioacoustics and cytogenetics - Zefa, Edison; Acosta, Riuler Corrêa; Timm, Vitor Falchi; Szinwelski, Neucir; Marinho, Marco Antonio Tonus; Da Costa, Maria Kátia Matiotti (Zootaxa, 2018)
In this paper we improve the morphological description of the tree cricket Neoxabea brevipes Rehn, 1913 and a new occurrence record for the species at the São Francisco de Paula National Forest Conservation Unit, State of Rio Grande do Sul, southern Brazil. Morphological characterization is provided together with illustrations emphasizing the most significant diagnostic features, such as the metanotal gland, abdominal specializations and phallic sclerites. The calling song was field recorded, comprising a continuous trill with dominant frequency of 3.6 kHz (19.7°C). The karyotype was described for the first time to Neoxabea Kirby, 1906, including diploid number of 2n=26, with two sexual chromosomes.